PENGARUH PENAMBAHAN FENOL FORMALDEHIDA TERHADAP SIFAT HARDBOARD KAYU CAMPURAN BERDASARKAN PENGELOMPOKAN BERAT JENIS - Rena M Siagian (Jurnal Penelitian Hasil Hutan, 1987)
This paper deals with an experiment on the effect  of phenol formaldehyde binder on the properties  of hardboard.  The boards were made of mixed wood species of five specific gravity groups  i.e.  < 0.30; 0.31-0.45; 0.46-0.60; 0.61-0.75 and >  0.75.Pulping employed  in the experiment  was the hot caustic soda,  and the sheets  were formed   by using the laboratory  wet felting  process.  The phenol formaldehyde blended at pulp  slurry and presipitated  by adding alum  to reach pH  ± 7.2. The amount  of phenol formaldehyde added during sheet formation  was made at 1, 1.5, and 2 percent  based on the oven dry pulp.The experimental  result indicated  that a quality panels  could be obtained  by adding 1. 5 percent  of phenol formaldehyde  binder. Increasing the phenol formaldehyde binder up to 2 percent  did not improved  the physico-mechanical  properties  of the board produced.   The experiment  also shows that better physico-mechanical  properties  of hardboard sheets  were obtained from 0.30 up to 0.60...0.75 specific gravity groups.  The panels made of wood with specific gravity more  than 0.75, appeared  to have inferior  quality.